Near-Field Imaging of an Inhomogeneous Cavity with a Modified Factorization Method (Journal of Computational Mathematics, 2024)
This paper is concerned with the inverse problem of scattering of time-harmonic acoustic waves by an inhomogeneous cavity. We shall develop a modified factorization methodto reconstruct the shape and location of the interior interface of the inhomogeneous cavityby means of many internal measurements of the near-field data. Numerical examples arecarried out to illustrate the practicability of the inversion algorithm.